"Obesity paradox" has not an impact on minimally invasive anatomical lung resection - Gómez-Hernández, María Teresa; Fuentes, Marta G; Novoa, Nuria M; Rodríguez, Israel; Varela, Gonzalo; Jiménez, Marcelo F (Cirugia española (English ed.), 2022)
The paradoxical benefit of obesity, the 'obesity paradox', has been analyzed in lung surgical populations with contradictory results. Our goal was assessing the relationship of body mass index (BMI) to acute outcomes after minimally invasive major pulmonary resections. Retrospective review of consecutive patients who underwent pulmonary anatomical resection through a minimally invasive approach for the period 2014-2019. Patients were grouped as underweight, normal, overweight and obese type I, II and III. Adjusted odds ratios regarding postoperative complications (overall, respiratory, cardiovascular and surgical morbidity) were produced with their exact 95% confidence intervals. All tests were considered statistically significant at p<0.05. Among 722 patients included in the study, 37.7% had a normal BMI and 61.8% were overweight or obese patients. When compared with that of normal BMI patients, adjusted pulmonary complications were significantly higher in obese type I patients (2.6% vs 10.6%, OR: 4.53 [95%CI: 1.86-12.11]) and obese type II-III (2.6% vs 10%, OR: 6.09 [95%CI: 1.38-26.89]). No significant differences were found regarding overall, cardiovascular or surgical complications among groups. Obesity has not favourable effects on early outcomes in patients undergoing minimally invasive anatomical lung resections, since the risk of respiratory complications in patients with BMI≥30kg/m and BMI≥35kg/m is 4.5 and 6 times higher than that of patients with normal BMI.